Pensar nuevas filosofías de la educación: un encuentro entre lo moderno y lo posmoderno (2014)
The article assumes thinking new philosophies of education from the encounter between the modern and the postmodern, and their description through some pedagogical practices in Colombia pedagogical knowledge. It analyzes a philosophy of education inspired by the transit of a philosophy of consciousness to a philosophy of language, as an alternative of reflection, as a topic of discussion and as a method to enable a comprehensive approach about human action and about education as a commitment to the other.